ความสัมพันธ์ระหว่างการกำกับดูแลกิจการกับค่าธรรมเนียมการสอบบัญชีของบริษัทจดทะเบียนในตลาดหลักทรัพย์แห่งประเทศไทย - รัตนา ชินโชติอังกูร (จุฬาลงกรณ์มหาวิทยาลัย, 2006)
The objective of this study is to investigate the relationship between corporate governance and audit fees of listed companies in The Stock Exchange of Thailand. The investigation is performed by applying Ordinary least Squares Regression (OLS) model with cross-sectional data of 267 listed companies in the period of 2003-2005. In regression model, the variables of duality, the proportion of independent directors, the proportion of family members in the board and the proportion of disclosure of corporate governance are used as a proxy of corporate governance. The result shows that duality is significantly and negatively associated with audit fees at 95% confidence. However, the proportion of independent directors, the proportion of family members in the board and the proportion of disclosure of corporate governance have no significant relationship with audit fees. The result also shows that size and type of audit firms have positive relationship with audit fees but liquidity and discretionary accruals have negative relationship with audit fees. In addition, industry type also has negative relationship with audit fees. Specific study of companies audited by Big 4 shows that the proportion of family members in the board is significantly and positively associated with audit fees at 95% confidence whereas study of companies audited by Non-Big 4 shows that the proportion of family members in the board is significantly and negatively associated with audit fees at 90% confidence.